Electronic payment adoption and consumers' spending growth: Empirical evidence from Nigeria - Lukman Oyeyinka Oyelami; Sulaimon Olanrewaju Adebiyi; Babatunde S. Adekunle (Future Business Journal, 2020)
The study investigates the determinants of electronic payment adoption and the role of electronic payment on con-sumers' purchase decisions as well as its effects on consumers' spending growth in Nigeria. To achieve this, both pri-mary and secondary data were deployed. The primary data were collected through a cross-sectional survey of banks' customers who have experienced the e-payment modes in Lagos state, Nigeria. The questionnaire was designed in line with Likert scale and validated. Fifty copies of the questionnaire were piloted. The copies retrieved were subjected to Cronbach alpha test of reliability. All the six variables were found to be reliable ranging between 0.725 and 0.828 Cronbach alpha values, which are within the acceptable limit. The sample size for this study, as determined through Cochran formulae is 384. In like manner, the instrument of data collection was administered on 420 respondents by using the multistage sampling technique to sample respondents across five divisions (locations) of Lagos. The data retrieved were analysed using descriptive (frequency and percentage) and inferential statistics (Pearson correlation, hierarchical regression analysis and analysis of variance). The results revealed that there is a positive significant rela-tionship between electronic payment systems determinants (convenience, security and safety, trust, social influence) and e-payment adoption in Nigeria. These variables accounted for more than half (3/5) of what influences consumers' adoption of e-payment mode of transaction in Nigeria. The results from the estimations show that factors such as educational attainment, financial inclusion, income level, internet service availability and other financial infrastructures such as point-of-sale machines and mobile banking services are critical determinants of e-payment adoption in Nige-ria. The results also indicate that electronic payment influences consumers' purchase decisions and thus increasing consumers' spending growth in Nigeria. The policy implication advanced by this study is that the Nigerian govern-ment can leverage on electronic payment to increase consumers' spending and thus improve aggregate demand which will consequently stimulate investment and economic growth in the country.
Keywords: G23; G2; E0; C5; 650; E-payment; Adoption; Growth; ARDL; Survey; Consumer spending; Nigeria